Parâmetros de eficácia do tratamento com análogos do GnRH em crianças portadoras de puberdade precoce. - FUJITA, Lívia Grimaldi Abud (2018)
The classic monitoring test to evaluate effectiveness of central precocious puberty (CPP) treatment is performed with acute GnRH and LH and FSH are collected every 30 minutes from its administration, up to 120 minutes. However, besides the acquisition of GnRH has become difficult, there is still no consensus in the literature on cut-off values for stimulated hormone levels indicating gonadotropic suppression. The cut-off values of LH for the diagnosis of CPP are less controversial, yet different authors suggest different values. Previous studies on UFTM has shown that this cutoff value can vary between 3.3 and 4.5 IU / L. The main objective of this study is to evaluate clinical and laboratory parameters that indicate suppression of the gonadotrophic axis and efficacy of the treatment of CPP with depot leuprolid acetate, a GnRH analog, as well as to determine which hormonal levels indicate gonadotrophic suppression. In addition, the effectiveness test was analyzed for its reproducibility and the need to be extended up to 2 hours. It has also been studied cutoff values for diagnosis of CPP. In this study were included twenty-four girls who were followed up at the Ambulatory of the Discipline of Endocrinology of UFTM for clinical and laboratory diagnosis of CPP under treatment with leuprorelin acetate, 3.75 mg, intramuscular every 28 days. The parameters considered as clinical efficacy of the treatment were regression or maintenance of secondary sexual characteristics according to Tanner, the decrease in growth velocity (GV), maintenance or decrease of the difference between bone age and chronological age (ΔBA-CA) and the maintenance or improvement of the final height prediction (FHP). The effectiveness test was carried out by dosing basal estradiol also FSH and LH at three time points: before and 1 and 2 hours after administration of leuprolide acetate 3.75 mg. It was repeated with a 28-day interval in 8 girls to evaluate the reproducibility of the test. In addition, the hormone levels measured in the test at different times were compared to each other to evaluate the need to extend the test up to 2 hours. To determine cutoff values that indicate diagnosis of CPP, the stimulus tests performed with leuprorelin acetate for diagnosis in the girls being treated were compared with the tests of 11 girls from a control group. Statistical analysis showed that there was a significant difference in the regression of the sexual characters according to Tanner and in the reduction of the GV. The ΔBA-CA and the FHP did not present alteration. The main variables used in the effectiveness test (stimulated LH) were reproducible and there was no statistical differencebetween the levels of LH dosed with 1 and 2 hours of test. Eleven girls showed improvement in all clinical parameters evaluated and when their effectiveness tests were compared to the others, the cutoff values were set to LH after 1 hour ≤ 3.64 IU / L and LH after 2 hours ≤ 6.10 IU /L as indicative of gonadotropic suppression. The values found for FSH and LH / FSH ratio were not reproducible or did not reach statistical significance. Regarding cut-off values for the diagnosis of PPC, hormonal levels compatible with gonadotropic activation were baseline estradiol> 12.8 pg / ml, baseline LH> 0.10 IU / L, LH after 1 hour> 2.66 IU / L and after 2 hours> 3.34 IU / L. Thus, the results of the study showed that it is possible to collect LH only one hour after the administration of leuprorelin and that values > 3.64 IU / L indicate a need for adjustment of the medication. In addition, collection of FSH during the effectiveness test is not required. Regarding the diagnosis of CPP, the cutoff values found in the study were similar to the results of studies previously performed at the UFTM.